Introducing thermoelectric generator concept to energy internet approach of electrical power system: Modeling analysis and assessment. (14th February 2022) - Satapathy, Priyambada; Mohanty, Pradeep Kumar; Sahu, Binod Kumar; Debnath, Manoj Kumar
Summary: With increase in environmental concerns, the idea of generating pollution‐free electricity like solar photovoltaic energy (SPV) is explored among researchers and industrialists. Despite the fact that photovoltaic is a direct and simple method of power production, it has lesser effectiveness in terms of quantum effect. The incident solar irradiance on the surface of the photovoltaic module heats the rear side of the module during the process of heat to electricity conversion giving rise to heating of the module and hence, rises its temperature. Nevertheless, when integration of solar PV system takes place, it suffers from the curse of being lower quantum efficient. Diverse integration of renewable sources makes the system complex, making regulating system parameters a difficult task; to avoid this, the system has been studied under incorporation of thermo electric generator (TEG) along with fuel cell technology (FCT) and in absence of TEG. This combined hybrid system generates substantial amount of electricity, which is helpful for residential application as well as to the utility. Nevertheless, the proposed system has only dc sources in order to make the system more reliable in terms of conversion, controlling, and feeding to the utility. Therefore, in this article, two systems have been studied and modeled, one is incorporated with TEG and another is without TEG. The performances of both the systems have been compared and analyzed on the basis of delivering real power and absorbing reactive power. It is evident from the study that the solar PV system with TEG has the ability of maintaining constant voltage at PCC terminals, absorbing lesser amount of reactive power and consequently delivering ample amount of real power without much complexity such as controlling of AC sources and grid activity. Around 41.0534% of higher real power has been supplied, and around 22.14% of lesser reactive power has been absorbed during the incorporation of TEG with this aforementioned hybrid system. On MATLAB‐based Simulink environment, the entire system has been studied, designed, and analyzed. Abstract : Diverse integration of renewable sources makes the system complex, making regulating system parameters a difficult task; to avoid this, the system has been studied under incorporation of TEG along with fuel cell technology (FCT) and in absence of TEG. The system has been studied under incorporation of TEG along with fuel cell technology (FCT) and in absence of TEG. Nevertheless, the proposed system have only dc sources in order to make the system more reliable in terms of conversion, controlling, and feeding to the utility. System has been delivering significant amount of real power to the utility, whereas greater amount of absorbed reactive power can be mitigated through the application of proposed system. Proposed System Diagram